Informator dla Kół Związkowych NSZZ "Solidarność" Region Mazowsze . no. 25-26, 1981 - [ed. Krystyna Romaniuk, Jan Gogacz, Zygmunt Maria Przetakiewicz] (NSZZ "Solidarność" Region Mazowsze, 1981)
Print run: 3500 copies